Efficacy of different intensities of percutaneous electrolysis for musculoskeletal pain: A systematic review and meta-analysis - Sánchez-González, Juan Luis; Navarro-López, Víctor; Cañada-Sánchez, Pablo; Juárez-Vela, Raúl; Viñaspre-Hernández, Regina Ruiz de; Varela-Rodríguez, Sergio (Frontiers in Medicine, 2023)
Objective: a meta-analysis of randomized controlled trials (RCTs) was conducted to determine the effect of of ultrasound-guided percutaneous electrolysis (PE) alone or as an adjunct to other interventions on pain intensity generated by musculoskeletal disorders, depending on the intensity of the technique. Dara Sources: PUBMED, EMBASE, Cochrane Library, Web of Science, SCOPUS, Health Medical Collection and CINALH from inception to September 2022 were searched to identify documents. Study selection: Publications investigating the effect of ultrasound-guided percutaneous electrolysis in musculoskeletal pain. Data extraction: data were extracted into predesigned data extraction and tables. Risk of bias was evaluated with the Cochrane Risk of Bias Tool (Rob 2.0). 13 articles met inclusion criteria. Data analysis: Random-effects meta-analysis models were used to quantify the difference in pain between the PE and control groups. Data Synthesis: A significant reduction in pain was found in favor of low (- 1.89; 95% CI: - 2.69; - 1.10; p <.001) and high intensity PE (-.74; 95% CI: - 1.36; - .11; p: .02) compared to control group. Low-intensity PE showed significant reduction in pain in the short (- 1.73; 95% CI: - 3.13; -. 34; p <.02) and long term (- 2. 10; 95% CI: - 2.93; - 1.28; p =.005;), with large effect sizes compared to control group. High-intensity PE only showed significant lower pain than control group in the long term (-.92; 95% CI: - 1.78; - .07; p <.03), with a small effect size, but not in the short term. Conclusions: We found small evidence suggesting a large effect of low-intensity PE for pain reduction compared with the control groups, both after treatment and at the end of follow-up. High-intensity percutaneous electrolysis showed a small effect size in pain reduction at the end of follow-up. This could indicate a greater efficacy in the treatment of musculoskeletal pain of the low-intensity modality versus the high-intensity modality.